UMKM Naik Kelas!: Pendampingan Laporan Keuangan dan Pelatihan E-Commerce OO Pizza Madiun di Era Ekonomi Kreatif - Maya Novitasari; Intan Dwi Maharani; Felita Ratna Dewanti; Rike Diah permatasari; Pasya Rizky Ramadhani; Alfina Nur Febriyani; Daffa Aliya Hanifah; Safina Aulia Arta mefia; Agil Alfiantikta Permata; Asysyfa Zahra Dwi Savira; Muchamad Fajar Yasam (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
This community service was driven to local MSMEs that face the digital era challenges, including marketing, product packaging, and financial management. The activity was carried out at MSME OO Pizzat, Madiun Regency. The aim is to assist MSME actors in improving their skills in using e-commerce platforms, enhancing product packaging design, and strengthening basic financial literacy. The implementation methods included interviews, direct mentoring, creating social media content, and digital publication. The activities were carried out in stages from June 17 to July 3, 2025. The program's results showed an increase in the partner's capacity for digital promotion through Instagram and TikTok, the installation of business banners, and a better understanding of financial recording and evaluation. This program applied the Objective and Key Results approach, which helped focus goals and measure the outcomes concretely. In conclusion, this program successfully promoted the digital transformation of MSMEs through practical and sustainable assistance.